Member of the Organiing Committee - Antoniou, Klitsa (My University, 2026)
Nomadifesta Keynote speakers: Ilan Wisgan, Antonis Danos and Mercedes Kemp Member of the Organizing Committee Sponsored by Cyprus Ministry of Culture and Education Organization of Conference and Workshops